Maternal disease, nutrition and social experience: consequences for the next generation - Curno, Olivia (2009)
Natural selection should favour individuals who are able to adjust their life history strategy and resource allocation in response to changing environmental and social conditions. I examined the flexibility of reproductive resource allocation by female mice in response to manipulation of their nutritional, immunological and social environment. I considered the consequences of their investment decisions for the next generation. In five separate experiments I found that: